2011
DOI: 10.5194/nhess-11-309-2011
|View full text |Cite
|
Sign up to set email alerts
|

Economic motivation of households to undertake private precautionary measures against floods

Abstract: Abstract. Flood damage is on the increase due to a combination of growing vulnerability and a changing climate. This trend can be mitigated only through significantly improved flood risk management which, alongside the efforts of public authorities, will include improvements in the mitigation measures adopted by private households. Economically "reasonable" efforts to self-insure and self-protect should be expected from households before the government steps in with publicly-funded relief programmes. To gain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
116
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(137 citation statements)
references
References 33 publications
4
116
2
1
Order By: Relevance
“…According to current German legislation, every potentially affected person has to do whatever is 'possible and reasonable' in order to mitigate flood damage (Wasserhaushaltsgesetz 2009:8, translated by author), and in the national climate adaptation strategy, the federal government states with regard to floods that the 'own precaution behaviour of the population must be strengthened ' (Die Bundesregierung 2008:23, translated by author). Empirical analyses from areas which have been flooded in the past have shown that mitigation can indeed effectively reduce economic flood damage considerably and is cost-efficient in many cases (Kreibich, Christenberger, and Schwarze 2011;Kreibich and Thieken 2008).…”
Section: Introductionmentioning
confidence: 99%
“…According to current German legislation, every potentially affected person has to do whatever is 'possible and reasonable' in order to mitigate flood damage (Wasserhaushaltsgesetz 2009:8, translated by author), and in the national climate adaptation strategy, the federal government states with regard to floods that the 'own precaution behaviour of the population must be strengthened ' (Die Bundesregierung 2008:23, translated by author). Empirical analyses from areas which have been flooded in the past have shown that mitigation can indeed effectively reduce economic flood damage considerably and is cost-efficient in many cases (Kreibich, Christenberger, and Schwarze 2011;Kreibich and Thieken 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there is an increasing demand for risk assessments that evaluate insights into hazards, consequences and vulnerabilities in an integrated way Thieken et al, 2014;Merz et al, 2014). Also, a good understanding of perceptual and behavioural aspects, possibly leading to higher or lower exposure and vulnerabilities, is needed for a comprehensive and sustainable risk management (Ludy and Kon-dolf, 2012;Bubeck et al, 2012Bubeck et al, , 2013Kreibich et al, 2011Kreibich et al, , 2015Collenteur et al, 2014;Holub et al, 2011;Di Baldassarre et al, 2013). Further complexity is added by the (projected) changes in climate, exposure and vulnerability (Merz et al, 2014;Bubeck et al, 2011;Jongman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated the effectiveness of these kinds of adaptation measures (Hudson et al, 2014;Kreibich et al, 2005Kreibich et al, , 2011Poussin et al, 2015), but also showed that the effectiveness of each measure very much depends on local 20 circumstances, for example, the characteristics of the flood (Hudson et al, 2014;Poussin et al, 2015). It is easy to imagine that mobile water barriers on doors and windows will have no effect once they are surpassed, whereas securing oil tanks against buoyancy will be effective, independent of flood water depth (Kreibich et al, 2011).…”
Section: Structural Adaptation and Hazard Reductionmentioning
confidence: 99%